Modeling and Simulation of CO2 Absorption into Promoted Aqueous Potassium Carbonate Solution in Industrial Scale Packed Column - Ali Altway; Susianto Susianto; Suprapto Suprapto; Siti Nurkhamidah; Nur Ihda Farihatin Nisa; Firsta Hardiyanto; Hendi Riesta Mulya; Saidah Altway (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
Carbon dioxide gas is a harmful impurity which is corrosive and it can damage the utilities and the piping system in industries. Chemical absorption is the most economical separation method which is widely applied in chemical industries for CO2 removal process. Hot potassium carbonate (K2CO3) is the most effective solvent that has been used extensively, especially for the CO2 separation process from gas synthesis and natural gas. This paper aims to develop mathematical model for investigating the CO2 absorption into promoted hot K2CO3 solution in industrial scale packed column in an ammonia plant. The CO2 was removed from the gas stream by counter-current absorption in two stages column. To represent the gas-liquid system, a rigorous mathematical model based on the two-film theory was considered. The model consists of differential mass and heat balance and considers the interactions between mass-transfer and chemical kinetics using enhancement factor concept. Gas solubility, mass and heat transfer coefficients, reaction kinetics and equilibrium were estimated using correlations from literatures. The model was validated using plant data and was used to compute temperature and concentration profiles in the absorber. The variation of CO2 recovery with respect to changes in some operating variables was evaluated. The effect of various kinds of promoters added into K2CO3 solution on the CO2 recovery was also investigated. The simulation results agree well with the plant data. The results of the simulation prediction, for the absorber pressure of 33 atm with a lean flow rate of 32,0867 kg/h, temperature of 343 K, and semi lean flow rate of 2,514,122 kg/h, temperature of 385 K, showed %CO2 removal of 95.55%, while that of plant data is 96.8%. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)